Use of Space and the Need for Planning in the Disaster-Prone Area of Code River, Yogyakarta, Indonesia - Rini Rachmawati; Charina Vertinia Budiarti (Faculty of Geography, Universitas Gadjah Mada, 2016)
Abstract The Code Riverbank is prone to flooding from lahars due to the regular eruption of Mount Merapi. The study focuses on the affected areas in Danurejan, Yogyakarta City, Indonesia. The purpose of this study is 1) to identify and analyze the use of space after the disaster, and 2) to analyze the action as well as spatial planning needs after the disaster. Data were collected from secondary and primary data. The primary data were obtained through observation, in-depth interviews, and focus group discussions. The results show that the utilization of space in the anticipation of the lahar flood disaster is still limited to the construction of an elevated levee. Research findings suggest attention should be brought to the utilization of space related to vulnerable groups. Also, public participation, preparation of design toward ecotourism and economic value, integration of risk analysis, and spatial distribution of risk should be aggregated into a detailed spatial plan. Abstrak Tepi Sungai Code merupakan daerah rawan terhadap banjir lahar yang disebabkan oleh erupsi Gunungapi Merapi. Penelitian ini menfokuskan pada daerah terdampak di Danurejan, Kota Yogyakarta, Indonesia. Tujuan dari penelitian ini adalah 1) untuk mengidentifikasi dan menganalisa fungsi ruang setelah bencana, dan 2) untuk menganalisa tindakan perencanaan ruang yang dibutuhkan setelah bencana. Data dikumpulkan dari data sekunder dan primer. Data primer diperoleh melalui observasi, interview mendalam, dan diskusi kelompok terfokus. Hasil menunjukkan bahwa pemanfaatan ruang dalam antisipasi dari bencana banjir lahar masih terbatas untuk pembangunan peninggian tanggul. Temuan penelitian menyarankan perlunya perhatian terhadap pemanfaatan ruang untuk kelompok yang rentan. Selain itu juga perlunya partisipasi publik dalam pemanfaatan ruang, penyiapan design ekowisata dan kegiatan bernilai ekonomi. Selan itu juga perlu adanya integrasi analisis risiko dan distribusi spasial dari risiko yang dituangkan dalam rencana rinci tata ruang.